Mobile computing theory and practice - Garg, Kumkum; Safari eBooks (Delhi : Dorling Kindersley (India), 2010)
"The book covers all basic concepts of mobile computing and communication and also deals with latest concepts like Bluetooth Security and Nokia Handhelds"--Resource description page.
Includes bibliographical references (p. 209) and index.
Keywords: Mobile computing; Portable computers; Electronic books